Socio-Environmental Factors Affecting Water Demand in Discrete Aboriginal Communities in Australia - Yuen, E.; James, I.; Taplin, Ross; Ho, G. (Inderscience Publishers, 2013)
Water use is a complex function of socioeconomic conditions and climatic factors. This paper considers the socio-economic and physical factors that need to be considered during the design of water supply systems to ensure appropriate supply systems are developed and local needs are met. Data was obtained for remote Indigenous communities located in the Northern Territory, Australia. Information from a census of community health and infrastructure needs and climatic data were correlated with water demand through multivariate linear regression analysis. This showed that average household size, climate, geographical location, essential service maintenance responsibility and remoteness of the community were correlated with water demand. It was particularly interesting to find that self-determination indicated by local or Indigenous management of water services was correlated with a reduction in water demand.